AN ANALYSIS OF HOUSE CONNECTION NETWORK CONTROL SHOP ON ENERGY LOSS USING PT PLN (PERSERO) ULP STABAT FORMULA JOGJA - Frandy Habeahan; Adi Sastra P Tarigan; Solly Aryza (Sean Institute, 2022)
This analysis aims to determine the number of energy losses that comes from the house connection. An Evaluation of house connections against connection standards that have been technically determined by the rules for Electricity and General Electrical Installation Requirements (PUIL) in 2000. Energy losses in the network are generally divided into two, namely technical losses and non-technical losses. The house connection is one of the contributing factors to technical losses. The method used in this research is the calculation of assets, existing customers, and data acquisition of load factor for feeders, and transformers at ULP Stabat. The results of the data obtained will determine the load factor on feeders, conductors, and substations. This calculation is calculated by the Jogja Formula which is the formula used at PLN until this journal was made.